Towards building a learning organisation in UiTM: an option / Faizul Haji Abdullah - Haji Abdullah, Faizul (Institute of Quality & Knowledge Advancement (InQKA), 2005)
Mature organisations, like old people, can become set in their ways. Universiti Teknologi MARA, in particular, has inherited decades of a unique mix of great traditions and norms. During its 45-years, it has experienced unprecedented waves of demands and expectations from the public, especially the Malay community in which the only constant is change. Those expectations have not stopped. Instead, they continue to sprout and increasingly change. Indeed, it is more challenging than before. This phenomenon, however, is not surprising since the Malay community have become more knowledgeable, and hence their expectations and aspirations, at times lead them to challenge the status quo. Compelled to meet such demands, UiTM is taking up these challenges in the quest to sustain its hallmark of an institution of higher learning for the Malay community, whilst maintaining the great unwritten traditions, norms and values. As an endorsement and in response to reaction from the outstanding community, UiTM has over the years made tremendous changes either in approach or system application, to maintain its position as the pride of the nation. However, as is apparent to the UiTM population, changes initiated by the management are not equally internalized, understood and shared by many within its community. Why is this so? If such a claim is true, then UiTM has to rethink, reassess and reinvent its approach so as to diffuse dogmatic perceptions from among its own citizenry, that translates into opposition against any of the change initiatives as a consequence of having visions which are not shared.The notable Senge's Fifth Discipline, reiterates that shared vision is the prime mover in developing shared meaning. In this context, when vision among the ditizenry is shared, it presumes that every individual should be able to manifest the purpose of existence towards the organisation's common destiny, with a "deep common purpose that expresses the organisation's reason for existence". However, contrary to this notion, how could everyone in the organisation be able to share the declared vision; and how could an individual manifest the defined vision and to be shared within his organisation? This argument is quite critical since the task of envisioning our purpose of existence should be flexible in nature; and this could possibly be developed through the establishment of a learning organisation.Therefore, as an introductory insight, the central theme of this paper is to promote learning organisation as an option for UiTM in managing its future by exploring the "management frontiers that make the difference" on how every citizen's learning capability can be enhanced from within and manifested consistently with the University's vision, and therefore allow the University to remain competitive.